Composite diaphragm, preparation method thereof and battery
By using functional coatings of porous ceramic particles and aqueous polyamide on the lithium-ion battery separator, the problem of the diaphragm shrinkage and ion transport obstacles at high temperatures is solved, high heat resistance and good electrolyte wetting are achieved, and the ion transport efficiency and low temperature performance of the battery are improved.
Patent Information
- Application Number
- CN202411471570.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-03-04
AI Technical Summary
Existing lithium-ion battery separators will experience shrinkage and ion transmission obstacles at high temperatures, resulting in reduced battery safety and inefficient ion transmission efficiency.
Porous ceramic particles and aqueous polyamide are used as functional coating materials, and the heat resistance of the membrane and electrolyte wetting are improved through the aqueous coating process, thereby enhancing the lithium ion transport efficiency.
The high heat resistance of the diaphragm and good electrolyte wetting properties are achieved, the lithium ion transmission efficiency is improved, the increase in the air permeability of the diaphragm is suppressed, and the low-temperature discharge performance of the battery is improved.
Smart Images

Figure BDA0005095904770000031 
Figure BDA0005095904770000081 
Figure BDA0005095904770000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a composite diaphragm, a preparation method thereof, and a battery. Background Art
[0002] Lithium batteries are mainly composed of positive electrodes, negative electrodes, separators, and electrolytes. With the current increasingly high performance requirements for lithium batteries in actual use, the demand for separators is no longer just to block direct contact between the positive and negative electrodes. Various functional separators continue to emerge, providing more choices for lithium-ion batteries. Improving safety and better ion transmission efficiency are the main functional requirements for lithium-ion battery separators. The main material of the separator is polyolefin. Due to the characteristics of the material itself, the polyolefin separator will shrink significantly at high temperatures. At the same time, the closed-cell shrinkage of the material due to heat affects ion transmission, which in turn causes safety accidents such as battery charging and discharging obstruction, positive and negative short circuits, and fires. In order to improve the heat resistance of the separator and maintain the ion transmission channel, surface coating is usually used.
[0003] Most of the diaphragm coating products on the market are divided into two categories, water-based coating and oil-based coating. Water-based coating basically uses inorganic particles as support, and relies on a binder to adhere to the surface of the diaphragm. The inorganic particles as the skeleton can support the diaphragm at a certain temperature, thereby reducing the shrinkage of the diaphragm. Based on this structure, smaller inorganic particles can be used with heat-resistant binder coating to improve the density of the coating and its tolerance to high temperatures, thereby playing a better supporting role. However, denser coatings and existing heat-resistant binders (such as polyacrylic acid) will cause the diaphragm permeability to increase significantly, affecting the electrolyte infiltration and blocking the ion transmission channel. Oily coatings such as aramid coatings have good heat resistance due to material properties, but the oil system process is difficult, the coating cost is high, and the environmental pollution is large, so it is not suitable for large-scale promotion. Summary of the invention
[0004] In view of this, the present invention provides a composite diaphragm and a preparation method thereof and a battery. The diaphragm has high heat resistance, effectively enhances electrolyte wettability, improves lithium ion transmission efficiency, effectively inhibits the increase of diaphragm air permeability, and improves battery low-temperature discharge performance. Moreover, the present invention can adopt a water-based coating process, avoiding the difficulty of using an oil-based coating process and the risk of high environmental pollution.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a composite membrane, the composite membrane comprising a substrate, and a functional coating disposed on at least one surface of the substrate;
[0007] The functional coating includes porous ceramic particles, waterborne polyamide and additives;
[0008] The particle size D of porous ceramic particles 50 It is 0.4~0.6μm.
[0009] In an embodiment of the present invention, the porous ceramic particles have a pore structure, and the pore diameter of the pore structure is 5 to 80 nm.
[0010] Preferably, the mass percentage of the porous ceramic particles in the functional coating is 50% to 98%.
[0011] Preferably, the mass percentage of the waterborne polyamide in the functional coating is 1% to 45%.
[0012] In an embodiment of the present invention, the auxiliary agent includes a binder, a dispersant, a thickener and a wetting agent.
[0013] In an embodiment of the present invention, the porous ceramic particles include but are not limited to at least one of aluminum oxide, boehmite, barium titanate, calcium oxide, magnesium oxide, zinc oxide, zirconium oxide, and silicon oxide.
[0014] In an embodiment of the present invention, the waterborne polyamide includes but is not limited to furan-based polyamide.
[0015] In an embodiment of the present invention, the binder includes but is not limited to at least one of polyacrylic acid, polyacrylate, polytetrafluoroethylene, styrene-butadiene rubber, polyacrylonitrile, and polyvinyl alcohol.
[0016] In an embodiment of the present invention, the dispersant includes but is not limited to at least one of polyether silane, polyacrylate, and polyacrylate salts.
[0017] In an embodiment of the present invention, the thickener includes but is not limited to at least one of polyvinyl alcohol, sodium carboxymethyl cellulose, polyurethane, acrylate, and sodium polyacrylate.
[0018] In an embodiment of the present invention, the wetting agent includes but is not limited to at least one of polyether-modified siloxane, modified succinic acid, and polyether-modified polydimethylsiloxane.
[0019] Preferably, the thickness of the functional coating is 1 to 5 μm.
[0020] In an embodiment of the present invention, the substrate includes at least one of polypropylene, polyethylene, polypropylene / polyethylene / polypropylene, polyvinyl chloride, polyamide, and glass fiber.
[0021] Preferably, the thickness of the substrate is 4 to 20 μm.
[0022] In a second aspect, the present invention provides a method for preparing the above-mentioned composite diaphragm, comprising the following steps:
[0023] S1, mixing porous ceramic particles, water-based polyamide, additives and water to obtain a functional coating slurry;
[0024] S2, coating the functional coating slurry on at least one surface of the substrate, and obtaining a composite diaphragm after drying.
[0025] In an embodiment of the present invention, the auxiliary agent includes a binder, a dispersant, a thickener and a wetting agent, and step S1 specifically includes:
[0026] S11, first mixing the porous ceramic particles, the dispersant, the water-based polyamide and water to obtain a first mixture;
[0027] S12, performing a second mixing of the first mixture and the thickener to obtain a second mixture;
[0028] S13, sand-grinding the second mixture to obtain a semi-finished slurry;
[0029] S14, performing a third mixing of the semi-finished product slurry, the binder and the wetting agent to obtain a functional coating slurry.
[0030] In an embodiment of the present invention, the sum of the amounts of porous ceramic particles, water-based polyamide, binder, dispersant, thickener and wetting agent is recorded as the total solid amount. Preferably, the mass ratio of the total solid amount to the amount of water is 1:(1-3).
[0031] In an embodiment of the present invention, the mass proportions of the components in the above preparation method are as follows:
[0032]
[0033] In a third aspect, the present invention provides a battery, which includes the above-mentioned composite diaphragm, or the composite diaphragm prepared by the above-mentioned preparation method.
[0034] In an embodiment of the present invention, the composite separator includes a functional coating disposed on one surface of a substrate, and the functional coating is in contact with a positive electrode sheet of a battery.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The present invention uses small-size ceramic particles with a porous structure as the skeleton of the coating material, making the coating denser and better supporting the diaphragm at high temperatures, so that the diaphragm has high temperature resistance; at the same time, the porous structure improves the liquid retention of the diaphragm through capillary action and a higher specific surface area, which can enhance the electrolyte wettability and improve the lithium ion transmission efficiency. The porous structure characteristics and the small particle size characteristics work together to effectively enhance the electrolyte wettability during the operation of the battery cell while ensuring the high heat resistance of the diaphragm, and at the same time improve the lithium ion transmission efficiency.
[0037] The present invention is further matched with modified water-based polyamide, which can also provide better coating heat resistance by relying on its polymer material characteristics; and the polar groups on the surface of the polymer material water-based polyamide can significantly improve the contact performance with the electrolyte, thereby improving the liquid absorption and improving the electrolyte wettability.
[0038] Therefore, the scheme of the present invention relies on the high temperature resistance of small-particle porous ceramics and water-based polyamide materials, the polymer characteristics of water-based polyamide, and the porous structure of ceramic particles to improve the liquid absorption and retention performance of the diaphragm, ensuring that the diaphragm has high heat resistance while effectively enhancing the electrolyte wettability, while improving the lithium ion transmission efficiency, effectively suppressing the increase in the diaphragm permeability, and improving the low-temperature discharge performance of the battery. The diaphragm of the present invention avoids the problem of too dense coating and too high permeability of the diaphragm caused by the use of small-particle ceramic particles when improving the thermal shrinkage performance of the diaphragm.
[0039] 2. The present invention can be prepared by a water-based coating process, thus avoiding the difficulty and risk of environmental pollution caused by using an oil-based coating process. DETAILED DESCRIPTION
[0040] The present invention discloses a composite diaphragm and a method for preparing the same and a battery. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0041] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0042] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0043] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0045] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0046] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0047] Specifically, the present invention adopts the following technical solutions:
[0048] In a first aspect, the present invention provides a composite membrane, the composite membrane comprising a substrate, and a functional coating disposed on at least one surface of the substrate;
[0049] The functional coating includes porous ceramic particles, waterborne polyamide and additives;
[0050] The particle size D of porous ceramic particles 50 It is 0.4~0.6μm.
[0051] In the embodiment of the present invention, the particle size D of the porous ceramic particles is 50 For example, the particle size D of the porous ceramic particles is 0.4 to 0.6 μm. 50 Any value among 0.4μm, 0.42μm, 0.44μm, 0.46μm, 0.48μm, 0.5μm, 0.52μm, 0.54μm, 0.56μm, 0.58μm, 0.6μm or any value within the range formed by any two of the above values. Within the above particle size range, the coating can be made denser, and the diaphragm can be better supported at high temperature, so that the diaphragm has high temperature resistance.
[0052] In an embodiment of the present invention, the porous ceramic particles have a pore structure, and the pore size of the pore structure is 5 to 80 nm. Exemplarily, the pore size of the pore structure is any value among 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, or any value within the range of values composed of any two of the above values. Within the above pore size range, the porous structure can improve the liquid retention of the diaphragm through capillary action and a higher specific surface area, which can enhance the wettability of the electrolyte and improve the lithium ion transmission efficiency. Preferably 5 to 50 nm.
[0053] Preferably, the mass percentage of porous ceramic particles in the functional coating is 50% to 98%. Exemplarily, the mass percentage of porous ceramic particles is 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or any value in the range of any two of the above values. Within the above content range, the coating is denser and plays a better role in supporting the diaphragm at high temperature, so that the diaphragm has high temperature resistance, high liquid retention rate, and high ionic conductivity. Preferably 80% to 95%, more preferably 87% to 95%.
[0054] Preferably, the mass percentage of waterborne polyamide in the functional coating is 1% to 45%. Exemplarily, the mass percentage of waterborne polyamide is any value among 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 20%, 30%, 40%, 45%, or any value within the range of any two of the above values. Within the above content range, better coating heat resistance and electrolyte wettability can be provided. Preferably 1% to 10%, more preferably 2% to 7%.
[0055] In an embodiment of the present invention, the auxiliary agent includes a binder, a dispersant, a thickener and a wetting agent.
[0056] In an embodiment of the present invention, the porous ceramic particles include but are not limited to at least one of aluminum oxide, boehmite, barium titanate, calcium oxide, magnesium oxide, zinc oxide, zirconium oxide, and silicon oxide.
[0057] In the embodiment of the present invention, the waterborne polyamide includes but is not limited to furan-based polyamide. Other types of waterborne polyamides are also within the protection scope of the present invention.
[0058] In an embodiment of the present invention, the binder includes but is not limited to at least one of polyacrylic acid, polyacrylate, polytetrafluoroethylene, styrene-butadiene rubber, polyacrylonitrile, and polyvinyl alcohol.
[0059] In an embodiment of the present invention, the dispersant includes but is not limited to at least one of polyether silane, polyacrylate, and polyacrylate salts.
[0060] In an embodiment of the present invention, the thickener includes but is not limited to at least one of polyvinyl alcohol, sodium carboxymethyl cellulose, polyurethane, acrylate, and sodium polyacrylate.
[0061] In an embodiment of the present invention, the wetting agent includes but is not limited to at least one of polyether-modified siloxane, modified succinic acid, and polyether-modified polydimethylsiloxane.
[0062] Preferably, the thickness of the functional coating is 1 to 5 μm. Exemplarily, the thickness of the functional coating is any value among 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any value within the range of any two of the above values. Preferably, it is 2 to 4 μm.
[0063] In an embodiment of the present invention, the substrate includes at least one of polypropylene, polyethylene, polypropylene / polyethylene / polypropylene, polyvinyl chloride, polyamide, and glass fiber.
[0064] Preferably, the thickness of the substrate is 4 to 20 μm. Exemplarily, the thickness of the substrate is any value among 4 μm, 7 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, or any value within the range formed by any two of the above values.
[0065] In a second aspect, the present invention provides a method for preparing the above-mentioned composite diaphragm, comprising the following steps:
[0066] S1, mixing porous ceramic particles, water-based polyamide, additives and water to obtain a functional coating slurry;
[0067] S2, coating the functional coating slurry on at least one surface of the substrate, and obtaining a composite diaphragm after drying.
[0068] In an embodiment of the present invention, the auxiliary agent includes a binder, a dispersant, a thickener and a wetting agent, and step S1 specifically includes:
[0069] S11, first mixing the porous ceramic particles, the dispersant, the water-based polyamide and water to obtain a first mixture;
[0070] S12, performing a second mixing of the first mixture and the thickener to obtain a second mixture;
[0071] S13, sand-grinding the second mixture to obtain a semi-finished slurry;
[0072] S14, performing a third mixing of the semi-finished product slurry, the binder and the wetting agent to obtain a functional coating slurry.
[0073] In an embodiment of the present invention, the sum of the amounts of porous ceramic particles, water-based polyamide, binder, dispersant, thickener and wetting agent is recorded as the total solid amount. Preferably, the mass ratio of the total solid amount to the amount of water is 1:(1-3). Exemplarily, the mass ratio of the total solid amount to the amount of water is any of 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3 or any value within the range of any two of the above values.
[0074] In an embodiment of the present invention, the mass proportions of the components in the above preparation method are as follows:
[0075]
[0076] For example, the mass percentage of the binder is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, or any value within the range of any two of the above values; the mass percentage of the dispersant is 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or any value within the range of any two of the above values; the mass percentage of the thickener is 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or any value within the range of any two of the above values. The mass percentage of the wetting agent is 0.03%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or any value within the range formed by any two of the above values.
[0077] In the embodiment of the present invention, the sanding material used for sanding includes but is not limited to 0.6-1 mm zirconium oxide beads.
[0078] In the embodiment of the present invention, the coating method includes but is not limited to gravure coating. Other coating methods can also realize the present invention.
[0079] Preferably, the drying temperature is 40-80° C. Exemplarily, the drying temperature is any value among 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., or any value within the range consisting of any two of the above values.
[0080] In a third aspect, the present invention provides a battery, which includes the above-mentioned composite diaphragm, or the composite diaphragm prepared by the above-mentioned preparation method.
[0081] In an embodiment of the present invention, the composite separator includes a functional coating disposed on one surface of a substrate, and the functional coating is in contact with a positive electrode sheet of a battery.
[0082] In an embodiment of the present invention, the battery is a lithium-ion battery.
[0083] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.
[0084] In the embodiment of the present invention, the battery further includes a negative electrode sheet, a positive electrode sheet, and an electrolyte. This application has no particular limitation on the negative electrode sheet, the positive electrode sheet, and the electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of this application can be achieved.
[0085] The reagents, instruments or materials used in the present invention can be obtained through commercial channels. Among them, furan-based polyamide was purchased from Anhui Lico New Material Technology Co., Ltd.
[0086] The present invention will be further described below in conjunction with embodiments:
[0087] Example 1
[0088] Weigh 10kg D 50 0.6μm porous alumina (porous ceramic particles, pore size of 5-50nm), 0.31kg furanyl polyamide (water-based polyamide), 0.13kg polyacrylate ammonium salt (dispersant), 15.95kg water are added to the double planetary stirring tank in sequence and fully mixed to obtain a premix. Then 2.96kg sodium carboxymethyl cellulose (thickener) glue (concentration of 1.5%, containing 0.044kg sodium carboxymethyl cellulose) is weighed and added to the premix, and the mixture slurry is fully stirred and dispersed to obtain a mixture slurry. The completely dispersed mixture slurry is added to a sand mill for sand grinding to obtain a semi-finished slurry. Thereafter, 2.46kg polyacrylic acid (concentration of 17.15%, containing 0.422kg of binder active ingredient) is weighed and added to the stirring tank containing the semi-finished slurry. After fully stirring and dispersing, 9.54g polyether modified siloxane (wetting agent) is added and stirred to obtain a finished slurry. Finally, the finished slurry was evenly coated on one side of a polyethylene substrate with a thickness of 7 μm by gravure coating, and dried at 45° C. to obtain a composite diaphragm including a functional coating.
[0089] Example 2
[0090] Weigh 11kg D 500.4μm porous alumina (porous ceramic particles, pore size of 5-50nm), 0.34kg furanyl polyamide (water-based polyamide), 0.14kg polyacrylate ammonium salt (dispersant), 17.56kg water are added to the double planetary stirring tank in sequence and fully mixed to obtain a premix. Then 3.25kg sodium carboxymethyl cellulose (thickener) glue (concentration of 1.5%, containing 0.049kg sodium carboxymethyl cellulose) is weighed and added to the premix, and the mixture slurry is fully stirred and dispersed to obtain a mixture slurry. The completely dispersed mixture slurry is added to a sand mill for sand grinding to obtain a semi-finished slurry. Thereafter, 2.71kg polyacrylic acid (concentration of 17.15%, containing 0.465kg of binder active ingredient) is weighed and added to the stirring tank containing the semi-finished slurry. After fully stirring and dispersing, 10.5g polyether modified siloxane (wetting agent) is added and stirred to obtain a finished slurry. Finally, the finished slurry was evenly coated on one side of a polyethylene substrate with a thickness of 9 μm by gravure coating and dried at 50° C. to obtain a composite diaphragm including a functional coating.
[0091] Example 3
[0092] Weigh 10kg D 50 0.5μm porous boehmite (porous ceramic particles, pore size of 5-50nm), 0.31kg furanyl polyamide (water-based polyamide), 0.13kg polyacrylic acid sodium salt (dispersant), 15.95kg water are added to the double planetary stirring tank in sequence and fully mixed to obtain a premix. Then 2.96kg sodium carboxymethyl cellulose (thickener) glue (concentration of 1.5%, containing 0.044kg sodium carboxymethyl cellulose) is weighed and added to the premix, and the mixture slurry is fully stirred and dispersed to obtain a mixture slurry. The fully dispersed mixture slurry is added to a sand mill for sand grinding to obtain a semi-finished slurry. Thereafter, 2.46kg polyacrylate (concentration of 17.15%, containing 0.422kg of binder active ingredient) is weighed and added to the stirring tank containing the semi-finished slurry. After fully stirring and dispersing, 9.54g polyether modified polydimethylsiloxane (wetting agent) is added and stirred to obtain a finished slurry. Finally, the finished slurry was evenly coated on one side of a polyethylene substrate with a thickness of 9 μm by gravure coating and dried at 50° C. to obtain a composite diaphragm including a functional coating.
[0093] Example 4
[0094] The only difference between this embodiment and embodiment 3 is that the amount of porous boehmite added is 9.79 kg, and the amount of water-based polyamide added is 0.52 kg.
[0095] Example 5
[0096] The only difference between this embodiment and embodiment 3 is that the amount of porous boehmite added is 9.58 kg, and the amount of water-based polyamide added is 0.72 kg.
[0097] Example 6
[0098] The only difference between this embodiment and embodiment 1 is that the coating thickness is 2 μm.
[0099] Example 7
[0100] The only difference between this embodiment and embodiment 1 is that the coating thickness is 4 μm.
[0101] Comparative Example 1
[0102] The only difference between this comparative example and Example 1 is that the ceramic particles used are D 50 It is conventional alumina with a particle size of 0.9 μm. Conventional alumina is solid particle with no pores on the surface or inside.
[0103] Comparative Example 2
[0104] The only difference between this comparative example and Example 1 is that the ceramic particles used are D 50 It is a porous alumina with a particle size of 0.3 μm.
[0105] Comparative Example 3
[0106] The only difference between this comparative example and Example 2 is that the ceramic particles used are D 50 It is conventional aluminum oxide of 0.4 μm.
[0107] Comparative Example 4
[0108] The only difference between this comparative example and Example 3 is that the amount of porous boehmite added is 10.3 kg, and water-based polyamide is not used.
[0109] Diaphragm and battery performance testing
[0110] 1. Diaphragm performance test
[0111] The composite membranes prepared in the above-mentioned embodiments and comparative examples were subjected to performance tests, including membrane air permeability, thermal shrinkage, liquid absorption rate, liquid retention rate, and ionic conductivity performance.
[0112] (1) Membrane air permeability test method:
[0113] Cut multiple samples from the coated mother roll along the transverse (TD) direction, and the width is ≥5cm. Use the Gurley 4340CJ air permeability tester to put the cut flawless samples into the sample port, press "ENTER" to start the test, measure the air permeability of the base film and the coating film, the difference between the two is the coating air permeability, and take the average of all coating air permeabilities as the average coating air permeability.
[0114] (2) Thermal shrinkage test method:
[0115] The diaphragm was cut into 100mm×100mm samples, and the samples were placed flat between the upper and lower layers of A4 paper. The samples were then placed in an oven at a test temperature of 130°C and baked for 1h. After the heating was completed, the samples were taken out and the sample dimensions (longitudinal MD and transverse TD) were measured again.
[0116] Shrinkage rate = (before shrinkage - after shrinkage) / before shrinkage × 100%
[0117] (3) Liquid absorption rate and liquid retention rate test method:
[0118] The diaphragm was cut into 100mm×100mm samples and weighed using an electronic balance to obtain the mass m1 before the test. The sample was then placed in a beaker filled with electrolyte and completely immersed. After leaving it for 2 hours, it was taken out and the residual electrolyte on the surface of the sample was wiped clean and weighed to obtain m2. The sample was then left to stand for 1 hour and weighed again to obtain m3.
[0119] Liquid absorption rate = (m2-m1) / m1
[0120] Liquid retention rate = (m3-m1) / m1
[0121] (4) Ionic conductivity test method:
[0122] Cut the diaphragm into 50mm×70mm samples, a total of 4 pieces, place the sample in a culture dish, pour the electrolyte, immerse the sample completely, seal it with plastic wrap, and place it in an environment with a water oxygen value of less than 20ppm for 2 hours. Block the electrodes with two stainless steel plates, and prepare the model in the order of electrode A-diaphragm-electrode B. Electrode A is connected to the reference electrode and the auxiliary electrode, and electrode B is connected to the working electrode and the sensing electrode. Use the AC impedance method for testing (AC Impednace). For the first time, put in 4 layers of diaphragms, smooth the diaphragms with tweezers, make a mold, press the weights onto the mold, make the electrode and diaphragm fit tightly, and start testing the AC impedance value, gradually reduce 1 layer at a time, and measure the AC impedance values R4, R3, R2, and R1 in turn. During the test process, it is necessary to ensure that the electrolyte in the mold can completely immerse the diaphragm. The conductivity of the diaphragm is calculated according to the following formula. When the linear fit R 2 If it is less than 0.995, retesting is required.
[0123] R= k×1 Formula (1)
[0124] P=(R×S) / d Formula (2)
[0125] σ=d / (R×S) Formula (3)
[0126] Where:
[0127] R is the resistance value of one layer of diaphragm, in ohms (mΩ).
[0128] k——fitting degree R 2 When >0.995, the slope of the curve
[0129] P is the resistivity of the diaphragm, in ohm-centimeters (mΩ·cm).
[0130] S——Effective area of diaphragm, in square centimeters (cm 2 ).
[0131] d is the thickness of one layer of diaphragm, in centimeters (cm).
[0132] σ——ionic conductivity of the membrane, in Siemens per centimeter (mS / cm).
[0133] 2. Battery assembly and performance testing
[0134] The composite diaphragm prepared in the above-mentioned embodiments and comparative examples is used to assemble the battery, and the commercial positive electrode sheet, the commercial negative electrode sheet, and the diaphragm are wound to obtain a bare battery cell, and the positive and negative electrode tabs are welded. The bare battery cell is installed in an aluminum-plastic film battery shell (or an aluminum battery shell / steel battery shell / nickel-plated battery shell), and liquid is injected, packaged, allowed to stand, formed, and capacity divided to obtain a lithium-ion secondary battery.
[0135] Perform a low-temperature DC internal resistance test on the assembled battery: at room temperature, charge at 1C constant current to 4.4V, then charge at 4.4V constant voltage until the current reaches 0.05C cutoff, then discharge at 1C constant current to 50% SOC, adjust the ambient temperature to -20℃, discharge at 0.36C for 30s, and record the discharge DC internal resistance.
[0136] The performance test results of the separator and battery are shown in Tables 1 and 2.
[0137] Table 1 Performance test results of diaphragm
[0138]
[0139]
[0140] Table 2 Battery performance test results
[0141]
[0142] From the above Example 1 and Comparative Example 1, it can be seen that under the same addition ratio, using D 50 Compared with solid ceramic particles with conventional particle size (0.9μm), the thermal shrinkage and liquid absorption and retention rate of 0.6μm porous ceramic particles are significantly improved. At the same time, the coating has less air permeability and a lower low-temperature DCR (direct current internal resistance).
[0143] From the above Example 1 and Comparative Example 2, it can be seen that under the same addition ratio, using D 50 Compared with 0.6μm porous ceramic particles D 50 It is 0.3μm porous alumina, and its thermal shrinkage and DCR are also low. When the particle size is too small, the support for the substrate is reduced. When the coating is too dense, the liquid absorption and retention performance is also reduced.
[0144] It can be seen from the above-mentioned Example 2 and Comparative Example 3 that, at the same addition ratio, the thermal shrinkage of porous ceramics is basically the same as that of conventional ceramics, but the air permeability value, ion conductivity and low-temperature DCR are significantly reduced; when water-based polyamide is not combined with porous ceramics, there are fewer gaps in small-particle ceramics, and there is no obvious improvement in liquid retention performance.
[0145] From the comparison of the above embodiments 3-5, it can be seen that when the addition ratio of water-based polyamide is adjusted, as the proportion of water-based polyamide increases, the air permeability value of the coating increases and the liquid absorption and retention rate decreases, but the thermal shrinkage performance of the diaphragm is significantly improved, and the DCR gradually decreases at low temperatures.
[0146] From the comparison between the above-mentioned Example 3 and Comparative Example 4, it can be seen that Comparative Example 4 does not use water-based polyamide and has poor heat shrinkage performance, liquid absorption rate, ionic conductivity and low-temperature DCR.
[0147] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A composite diaphragm, characterized in that: The composite diaphragm includes a substrate, and a functional coating disposed on at least one surface of the substrate; The functional coating comprises porous ceramic particles, water-based polyamide and additives; The particle size D of the porous ceramic particles 50 It is 0.4~0.6μm.
2. The composite diaphragm according to claim 1, characterized in that: The porous ceramic particles have a pore structure, and the pore diameter of the pore structure is 5 to 80 nm.
3. The composite diaphragm according to claim 1, characterized in that: The mass percentage of the porous ceramic particles in the functional coating is 50% to 98%; Preferably, the mass percentage of waterborne polyamide in the functional coating is 1% to 45%; Preferably, the auxiliary agent includes a binder, a dispersant, a thickener and a wetting agent.
4. The composite diaphragm according to claim 3, characterized in that: The porous ceramic particles include at least one of aluminum oxide, boehmite, barium titanate, calcium oxide, magnesium oxide, zinc oxide, zirconium oxide, and silicon oxide; Preferably, the waterborne polyamide comprises furan-based polyamide; Preferably, the binder includes at least one of polyacrylic acid, polyacrylate, polytetrafluoroethylene, styrene-butadiene rubber, polyacrylonitrile and polyvinyl alcohol; Preferably, the dispersant includes at least one of polyether silane, polyacrylate, and polyacrylate; Preferably, the thickener includes at least one of polyvinyl alcohol, sodium carboxymethyl cellulose, polyurethane, acrylate, and sodium polyacrylate; Preferably, the wetting agent includes at least one of polyether-modified siloxane, modified succinic acid, and polyether-modified polydimethylsiloxane.
5. The composite diaphragm according to claim 1, characterized in that: The thickness of the functional coating is 1-5 μm.
6. The composite diaphragm according to any one of claims 1 to 5, characterized in that: The substrate comprises at least one of polypropylene, polyethylene, polypropylene / polyethylene / polypropylene, polyvinyl chloride, polyamide, and glass fiber; Preferably, the thickness of the substrate is 4 to 20 μm.
7. The method for preparing the composite diaphragm according to any one of claims 1 to 6, characterized in that: The steps include: S1, mixing porous ceramic particles, water-based polyamide, additives and water to obtain a functional coating slurry; S2, coating the functional coating slurry on at least one surface of the substrate, and obtaining a composite diaphragm after drying.
8. The preparation method according to claim 7, characterized in that: The auxiliary agent includes a binder, a dispersant, a thickener and a wetting agent. Step S1 specifically includes: S11, first mixing the porous ceramic particles, the dispersant, the water-based polyamide and water to obtain a first mixture; S12, performing a second mixing of the first mixture and the thickener to obtain a second mixture; S13, sand-grinding the second mixture to obtain a semi-finished slurry; S14, performing a third mixing of the semi-finished product slurry, the binder and the wetting agent to obtain a functional coating slurry.
9. The preparation method according to claim 8, characterized in that: The sum of the amounts of porous ceramic particles, water-based polyamide, binder, dispersant, thickener and wetting agent is recorded as the total solid amount, and the mass ratio of the total solid amount to the amount of water is 1:(1-3); And / or, the mass proportions of the components are as follows:
10. A battery, characterized in that: The battery comprises the composite diaphragm according to any one of claims 1 to 6, or the composite diaphragm prepared by the preparation method according to any one of claims 7 to 9; Preferably, the composite separator comprises a functional coating disposed on one surface of a substrate, and the functional coating is in contact with the positive electrode sheet of the battery.
Citation Information
Patent Citations
Novel ceramic coating polyolefin composite film and preparation method thereof
CN103811702A
Preparation and application of water-based coating slurry for improving diaphragm rupture temperature
CN116387751A
Coating agent composition, separator formed by using coating agent composition, and battery using separator
KR1020140076784A